PENGARUH GOOD CORPORATE GOVERNANCE, TINGKAT PEMAHAMAN AKUNTANSI, DAN PEMANFAATAN TEKNOLOGI INFORMASI TERHADAP KUALITAS LAPORAN KEUANGAN - Astuti, Ni Kadek; Padnyawati, Kadek Dewi (Hita Akuntansi dan Keuangan, 2022)
This paper was written with the hope that later it can reveal the relationship between Good Corporate Governance, Accounting Understanding Levels, and Utilization of Information Technology with Quality Financial Reports at Village Credit Institutions (LPD) in Tegallalang District. The population in this study were all LPDs that were still operating in Tegallalang sub-district, which amounted to 39 LPDs, and 6 LPDs that were not active with a total of 290 employees. The results of this study indicate that the quality of financial reports can increase due to the increase in good corporate governance, level of accounting understanding , Utilization of information technology in an LPD. In the future, the results of this study can be used as material for consideration in designing regulations and policies related to improving the quality of financial reports.